Formation and Stability of Substituted Pyromorphite: A Molecular Modeling Study - Abhijit V. Shevade; Larry Erickson; Gary Pierzynski; Shaoyi Jiang (Journal of Hazardous Substance Research, 2001)
Soils contaminated with lead pose significant risk to human as well as terrestrial and aquatic ecosystems. Theoretical phase relationships and field observations suggest that the interaction of lead and phosphorus to form pyromorphites Pb5(PO4 )3 X (X= OH-, Br-, Cl-, or F-) is an important buffer mechanism controlling the migration and fixation of lead in the environment. We report a molecular modeling approach to investigate the formation and stability of the substituted pyromorphites, which involved evaluating the lattice energy of the minerals using ab initio quantum mechanics. The lattice energy values are used in a Born-Haber thermodynamic cycle to calculate the heat of formation of the minerals. The Gibbs free energy of the substituted pyromorphites is then calculated from the change in entropy and heat of formation. The systems investigated in this study include partial and total substitution of Pb2+ by Cd2+ and Zn2+ cations in chloropyromorphite (Pb5(PO4 )3Cl ). Results indicate the unstable nature of the substituted Pb pyromorphite. The stability of the substituted minerals is found in the order Pb-pyromorphite > Cd-pyromorphite > Zn-pyromorphite.
Keywords: pyromorphite; substitution; stability; formation; molecular modeling